Resistance to Interlocking Power Structures Among Adult Educators - Ming-Yeh Lee; Doris Flowers; Vanessa Sheared (Adult Education Research Conference, 2002)
Six graduate students were interviewed and focus was given to how the education they received impacted the ways in which they addressed issues of power and control in their own classrooms. Awareness of unequal power structures in the classroom, written words matter, lived experiences and moving from theory to practice were themes that emerged from the data.